2016
DOI: 10.15376/biores.11.1.2684-2697
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Incorporation of Nano-Bamboo Charcoal on the Mechanical Properties and Thermal Behavior of Bamboo-Plastic Composites

Abstract: To illustrate the effects of nano-bamboo charcoal (NBC) on the properties of bamboo plastic composites (BPC), nano-bamboo charcoalbamboo plastic composites (NBC-BPC) were prepared at 0%, 2.5%, 5%, 7.5%, 10%, and 12.5% (w/v) NBC and characterized. The effects of NBC on the water absorption, fractured surfaces, mechanical properties, and thermal properties of the composites were investigated. NBC had strong interfacial interaction in the BPC, which greatly improved the interfacial adhesion of bamboo flour (BF) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Because BC is very porous, polymers can permeate these pores, strengthening the BC-polymer interface and thus enhancing the mechanical properties of the composites. Li et al (2014) reported that the mechanical properties, water resistance, and thermal properties of WPC with BC were higher than WPCs, and Zhu et al (2016) also found the same results while the BC nanoparticles enhance BPCs. You et al (2014) reported a strong interfacial interaction between BC and polymers because the tanδ decreased with an increase in the BC content.…”
mentioning
confidence: 73%
See 4 more Smart Citations
“…Because BC is very porous, polymers can permeate these pores, strengthening the BC-polymer interface and thus enhancing the mechanical properties of the composites. Li et al (2014) reported that the mechanical properties, water resistance, and thermal properties of WPC with BC were higher than WPCs, and Zhu et al (2016) also found the same results while the BC nanoparticles enhance BPCs. You et al (2014) reported a strong interfacial interaction between BC and polymers because the tanδ decreased with an increase in the BC content.…”
mentioning
confidence: 73%
“…0.000** *Significant difference at the 95% level; **significant difference at the 99% level; ns= not significant PEER-REVIEWED ARTICLE bioresources.com Chen et al (2016). "Bamboo/PE composites," BioResources 11(4), 9986-10001.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations